2015
DOI: 10.1176/appi.ajp.2014.14060723
|View full text |Cite
|
Sign up to set email alerts
|

Narcissistic Personality Disorder: Diagnostic and Clinical Challenges

Abstract: See related features: Clinical Guidance (Table of Contents) and AJP Audio (online).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(159 citation statements)
references
References 42 publications
3
126
0
9
Order By: Relevance
“…Narcissistic personality disorder spans a spectrum, ranging from high-functioning to malignant subtypes, is difficult to treat and requires longer-term treatment such as transference- or schema-focused psychotherapy and dialectical behavioral therapy54 ) . It is unknown whether this also applies to the burned out person with maladaptive narcissism (not narcissistic personality disorder).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Narcissistic personality disorder spans a spectrum, ranging from high-functioning to malignant subtypes, is difficult to treat and requires longer-term treatment such as transference- or schema-focused psychotherapy and dialectical behavioral therapy54 ) . It is unknown whether this also applies to the burned out person with maladaptive narcissism (not narcissistic personality disorder).…”
Section: Resultsmentioning
confidence: 99%
“…It is unknown whether this also applies to the burned out person with maladaptive narcissism (not narcissistic personality disorder). Nonetheless, these persons will probably benefit most from any such oriented therapies if an exhaustive life engagement is discussed as a consequence of trying to maintain a self-perception of being exceptional (in fantasy or behavior) because of a fragile sense of self54 ) . Moreover, therapists may try to uncover maladaptive narcissism as a dysfunctional strategy for keeping up with an illusory self-image as a grandiose person, so to eventually turn maladaptive into adaptive behaviors4 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have examined the impact of NPD on the psychotherapeutic relationship. 1214 Tanzilli and colleagues 14 found that individuals treating patients with NPD were more likely to experience negative counter-transference feelings of disengagement as well as feeling criticized or mistreated. These authors highlight the core feature of narcissism—struggle to form intimate relationships—as a significant barrier to positive treatment outcome, due to the patient’s potential inability to form a safe and trusting relationship with the therapist.…”
Section: Introductionmentioning
confidence: 99%
“…An empathic approach acknowledges the patient's intense emotional response to the challenges of hospitalization without frustration and judgment. Maintaining an empathic—or even simply neutral—stance can avoid a power struggle and also improves the therapeutic alliance with the patient …”
Section: Behavioral Interventionsmentioning
confidence: 99%